Regional Non-point Source Pollution Control Method: A Design of Ecological Compensation Standards - Lu, Shibao; Zhong, Weijun; Li, Wei; Taghizadeh-Hesary, Farhad (Frontiers in Environmental Science, 2021)
Reasonable ecological compensation standard is the key to solve farmland non-point source pollution. In the design of compensation standards, the current investigation included ecological benefits in selecting the experimental method. The Multinomial Logit model is used to analyze the willingness of farmers to receive compensation for non-point source pollution control of cultivated land. The results are as follows: 1) Financial compensation can effectively stimulate farmers’ willingness to control non-point source pollution. 2) The willingness of farmers to participate in the ecological compensation is greater when there prevails a higher level of risk preferences and higher understanding of farmland non-point source pollution control policy. Also, willingness is higher in younger, highly educated, and highly involved in a part-time family business with higher recognition degree in the ecological function of farmland non-point source pollution control. 3) The difference in treatment measures and compensation methods should be included in the standard compensation design. Therefore, the design of the ecological compensation standard should take into account the economic loss and ecological benefits of farmers at the same time, and environmental protection publicity and education for farmers can also be carried out with the help of modern media.